2018
DOI: 10.1093/ecco-jcc/jjy100
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Effect on the Health-related Quality of Life of Inflammatory Bowel Disease Patients: A Systematic Review With Meta-analysis

Abstract: Herein we prove that placebo effect on HRQoL is meaningful, providing insights about implications for clinical trials' design and interpretation and for IBD management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The overall sample size ( n ) was 5365, 44% on placebo. The majority of studies were parallel (85%), single-center (60%, indicated in k = 78), and double-blind (only one single-blind [ 57 ] and none was open) with two arms (88%) and small sample sizes (median 45, interquartile-range [ 30 91 ]). About half of the studies (48%) had a duration of 12 weeks or more and three less than 4 weeks [ 57 – 59 ] (median 10 weeks [ 8 12 ]) as well as half used a fixed dose schedule (51%, k = 84) and had a washout from psychotropic drugs (55%, k = 75), yet definitions and duration varied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall sample size ( n ) was 5365, 44% on placebo. The majority of studies were parallel (85%), single-center (60%, indicated in k = 78), and double-blind (only one single-blind [ 57 ] and none was open) with two arms (88%) and small sample sizes (median 45, interquartile-range [ 30 91 ]). About half of the studies (48%) had a duration of 12 weeks or more and three less than 4 weeks [ 57 – 59 ] (median 10 weeks [ 8 12 ]) as well as half used a fixed dose schedule (51%, k = 84) and had a washout from psychotropic drugs (55%, k = 75), yet definitions and duration varied.…”
Section: Resultsmentioning
confidence: 99%
“…Recent instruments have also been developed, among others the Brief Observation of Social Communication Change (BOSCC) [ 86 , 87 ], the Autism Behavior Inventory [ 88 ], and the Autism Impact Measure (AIM) [ 89 ], but their utilization is yet to be determined. Patient- (or parent-) reported outcomes have also gained recently greater attention [ 90 ], yet they should not be considered immune to placebo-effects [ 91 ]. The utilization of scales that require more extensive training and experience (e.g., ADOS, BOSCC, and VABS) might be challenging in larger scale trials, and thus a low inter-rater reliability could increase the variance of measurements and subsequently decrease drug-placebo differences.…”
Section: Discussionmentioning
confidence: 99%
“…Increased placebo response can also be expected when instead of biomarkers and clinical disease signs, subjective, patientreported outcomes (PRO) are used to assess the clinical efficacy of an intervention-this was shown in a meta-analysis of 16 RCTs in IBD (11 UC and 15 CD) in which IBS-specific (IBDQL) and generic (SF36) health-related quality of life was measured as the primary outcome (Estevinho et al, 2018): while overall drug-over-placebo benefit was maintained, the placebo response rates were high with 41% for clinical improvement and 31% for remission. This effect is as well established in the literature, but for many diseases, appropriate biomarkers are unfortunately missing.…”
Section: Predictors Of the Placebo Responsementioning
confidence: 99%
“…This decision was made because the design of randomized controlled trials reduces bias by minimizing confounds between patient groups (due to randomization) and by controlling for placebo effects on HRQoL, which have been demonstrated to be substantial in studies of patients with UC. 52 However, by restricting our evidence base to only randomized controlled trials, we limit the generalizability of our findings and ignore data that could be relevant to the question of the degree to which IBDQ-32 scores are sensitive to the clinically efficacious UC treatments. Future research incorporating findings from studies using nonrandomized design could potentially provide additional information with respect to the research questions addressed in this review.…”
Section: Limitationsmentioning
confidence: 99%